Human Capital Flight: A Woe to Nigeria’s Economic Development - Kaku, Mohammed; Kele, Ali; Jijji, Mohammed Mohammed; Goni , Umar Mohammed; Aliyu, Aliyu Sabo (Kashere Journal of Politics and International Relations, 2025)
Globally, it remains an indisputable fact that, country’s future is mostly dependent on its human resources both educated and talented citizens; they are the country’s greatest asset and should be cherished above all other endowed resources, including oil, agriculture and all other natural resources. Nigeria is a good example, blessed with both human and material resources. It is indisputable that, development of a country hinges largely on the quality of human resources and not just presence of natural resources. The plague of Nigerian migration to industrialized countries, which has resulted in brain drain in many facets of our national life, makes this issue even more difficult to handle the extent of the specialists’ migration. The magnitude of skilled and knowledgeable people leaving Nigeria poses a threat to the country’s overall progress and development. This study therefore demonstrates that when there is a significant degree of expert migration from Nigeria, national progress and development cannot be realized. The causes of this widespread Nigerian migration based on corruption, has resulted in a rise in unemployment and a harsh economic situation which result in difficult livelihood situation. The study also shows how migration affects all facets of the political system. The study concludes that if the increasing tendency of competent Nigerians migrating abroad is not addressed, Nigeria’s progress and development will not be attainable.